Online psychological care on the context of Covid-19 in Paraíba (Research, Society and Development, 2023)
Online pscychological care was necessary to attend the mental health demands of general population and health professionals during the Covid-19 pandemic. The CFP guided the suspension of face-to-face treatment, orienting the performance of psychology to be in the online modality with the use of ICTs, soon after the disease was classified as a pandemic. So, this research aims to analyze the self-reported experience of these professionals in their remote work during the Covid-19 pandemic. A cross-sectional, exploratory and descriptive research of quantitative-qualitative nature, the sample focus psychologists from the state of Paraiba who attended online in the period between March and September of 2020. For data collection, a sociodemographic questionary and individual interviews were used. The interviews were submitted to the Iramuteq software, which resulted in five categories interpreted in the light of content analysis. It was observed that psychological professionals faced challenges in this transition, both personal and professional in their lives. However, it was a period of experience and evolution towards online psychological care.